Strategi Pengembangan Usaha dan Peningkatan Kinerja UMKM di Masyarakat Kecamatan Selesai Kabupaten Langkat - Endri Dores (Maslahah: Jurnal Pengabdian Masyarakat, 2022)
Micro, Small and Medium Enterprises (MSMEs) have the potential to increase income and absorb labor. This community service aims to develop businesses and improve employee performance by looking for business development strategies and MSME Performance Improvements that can be used to increase people's income, so that they can obtain maximum profit so that the business can continue to grow to increase income, including increasing the income of the people who work at the dry tofu factory. business development strategy and improving the performance of MSMEs by improving and maintaining product quality, maintaining product cleanliness and customer satisfaction with the products offered. From the results and discussion, it can be concluded that the Business Development Strategy and Performance Improvement of Community MSMEs in the Selesai District, Langkat Regency will experience developments that continue to improve, these MSMEs have an important role in improving community welfare and increasing the income of the surrounding community so that they can meet their daily needs. such as food, as well as other needs such as shelter, family health, the need for their children's education, and other needs.